Salah al-Din al-Ayyubi (1174-1193) : his rise, achievements and implementation of justice - Nurina Syazana Aznam (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
Salah al-Din al-Ayyubi was a well-known figure in the Islamic history. He was the Muslim ruler of Egypt, Syria, Yemen, and Palestine, and he grew up in a good and religious environment. Salah al-Din was known as a religious person, a nobleman, and a devout Muslim. He spent most of his life attempting to unite the Muslim dynasty rather than fighting the crusaders. Salah al-Din believed that if Muslims united together, they would become stronger. One of his most significant achievements was the liberation of Jerusalem, which ended the Crusaders' 88-year occupation. His determination to establish justice and ensuring that his people were treated properly, regardless of their faith, skin colour, or background, was one of his defining characteristics. Salah al-Din al- Ayyubi 's personality drew a lot of attention from both the Muslim and Western worlds, and both highly respected him. Considering his personality, this thesis examines the historical context that led to the emergence of Salah al-Din al-Ayyubi, analyses his leadership and governance, and identifies the implementation of justice under his reign. The study uses a qualitative approach by conducting library research to gather information on the subject. The methodology adopted in this study was by analyzing historical primary and secondary records in order to acquire a complete understanding of Salah al-Din al-Ayyubi’s character. Most of the study focused on the third crusade, where there were various and fierce battles between the Muslim dynasty and the Christian kingdom during this time. The study also identified the definition of justice from the Islamic perspective by providing Quranic verses on the importance of justice in Islam. All in all, the study discovered that justice can be applied to oneself as well as to others, regardless of their status, religion, or background. This study was significant to obtain an understanding of justice and its practices throughout Salah al-Din al-Ayyubi 's reign and how justice was administered in the government at the time.